Large CP violation in flavor violating muon decays - Diego Redigolo; Michele Tammaro; Andrea Tesi (European Physical Journal C: Particles and Fields)
Abstract We identify new room for CP violation in lepton flavor violating observables not bound by the electric dipole moment of leptons. By focusing on new physics in the muon-electron sector, we show that CP violation can make its first appearance in lepton flavor violating muon decays rather than in the electric dipole moment of the electron, further motivating the experimental program of Mu3e. We tackle this issue by performing the full one-loop running and matching from the low energy observables at the muon scale, including the T-odd asymmetry in $$μ → 3e$$ μ → 3 e decays, to the Standard Model effective field theory above the electroweak scale. We then sketch a simple UV model that can give rise to these patterns.